The social dynamics of organizational justice - Steiner, Dirk D.; Skarlicki, Daniel P.; Gilliland, Stephen (Research in social issues in management., 2015)
This eighth volume in the Research in Social Issues in Management series explores a variety of social relations to expand our thinking about organizational justice, which is fundamentally based on relationships between organizational authorities and the employees of the organizations. These relationships also emphasize the roles of various actors and suggest fairness perspectives other than that of subordinates' perceptions of the treatment received from their superiors.The 10 chapters of the volume are divided into two major sections plus a conclusion. The first section presents five chapters that bring new theoretical perspectives to bear on justice considerations. Topics treated throughout this section include conflicting perspectives on justice, psychological distance, greed, and punishment. The second section places emphasis on leaders' or managers' perspectives of justice, going back to some of the initial proactive roots of justice rather than on what has become the more traditional focus, that of subordinate perceptions or reactive justice. In the contributions comprising this section, leaders' personalities, their motives, and their position as both superiors of some employees and subordinates of their own superiors are examined to provide new perspectives on the leadership role in justice matters.The concluding chapter, by Brockner and Carter, comments on the collection of chapters and proposes extensions and alternative perspectives for consideration. This commentary chapter suggests that the volume surfs a fifth wave in the history of justice research as these chapters all examine justice as a dependent variable influenced by numerous factors.